'Codington', a High‐Yielding, High‐Quality, Large‐Seeded Soybean. Issue 1 (13th December 2013) - Jiang, Guo-Liang; Scott, Roy A.; Green, Marci; Wang, Xianzhi; Bhusal, Siddhi; Zhang, Jiaoping; Hall, Nicholas
Abstract : Soybean [ Glycine max (L.) Merr.] 'Codington' (Reg. No. CV‐511, PI 667736) was developed at South Dakota State University (SDSU), Brookings, SD. It was released by the South Dakota Agricultural Experiment Station in April 2013 for high yield, a large seed with high protein and oil content suitable for soy food production. Codington (experimental line SD04CV‐611) is a late maturity group (MG) 0 cultivar (relative maturity 1.0). It originated from the F5 progeny of a single F4 plant derived from the cross of 'Surge' × A96‐591033 by a modified single‐seed descent method. Following yield trials within the SDSU soybean breeding program, it was evaluated for yield and quality through the USDA Northern Regional Uniform Soybean Tests (UT) in 2007 to 2010 and South Dakota Crop Performance Tests (CPT) in 2010 to 2012. Over all 36 environments, the yield of Codington averaged 3611.3 kg ha −1, 1.2% higher than the check cultivar Surge. In the UT tests (24 year‐locations), Codington also exhibited an average yield 2.9% higher than the check cultivar Sheyenne. The average protein and oil content of Codington for the UT tests (22 year‐locations) was 365.3 and 174.4 g kg −1 at 13% moisture, compared with Surge (364.0 and 174.4 g kg −1 ) and Sheyenne (342.0 and 178.2 g kg −1 ). Its 100‐seed weight was 21 g. Codington is a conventional, high‐yield, high‐quality (relatively higher protein and oil concentration as well as good visual seed quality), MG 0 cultivar with large seeds, and thus it is particularly suitable for soy food production in South Dakota and similar regions.